Clinical Presentation and Aetiology of Myelopathy (TAJ: Journal of Teachers Association, 2018)
Introduction: Diseases of the spinal cord are called myelopathy. They are frequently devastating. They produce quadriplegia or paraplegia with sensory deficits far beyond the site of damage. Many spinal cord diseases are reversible if recognized and treated at an early stage.Objectives: The aim of this study was to evaluate clinical presentation and aetiology of myelopathy among the patients attending Rajshahi Medical College Hospital with the help of history, clinical examination and investigations.Methodology: This was a cross-sectional type of descriptive study. A total 44 myelopathic patients were evaluated between January 2009 to December 2009.Result: Out of 44 patients, 33 (75%) were male and 11 (25%) were female (ratio 3:1), mean aged 35 ± 13.9 years (range 13-65 years). Among them 24 (54.5%) patients had paraparesis and 20 (45.5%) patients had quadriparesis. It was observed that majority 33 (75%) of them had compressive type and 11 (25%) patients had non-compressive type of involvement. Out of 33 compressive myelopathy, the commonest cause was cervical spondylotic myelopathy 14 (42.4%) in number. 2nd cause was Pott’s disease 8 (24.2%) in number. Syringomyelia was detected in 5 (11.4%) patients, disc herniation was in 2 (6.1%) patients, schwannoma was in 2 (6.1%) patients, lipoma was in 1 (3%) patient and 1 (3%) patient was metastasis to the vertebra. Out of 11 non-compressive myelopathy, acute transverse myelitis was detected in 9 (81.8%) patients and familial spastic paraplegia in 2 (18.2%) patients.Conclusion: All patients with myelopathy should be investigated for potentially treatable causes.TAJ 2013; 26: 48-52